Long-Term Durability Studies on Chemically Treated Reclaimed Asphalt Pavement Material as a Base Layer for Pavements. Issue 1 (January 2017) - Puppala, Anand J.; Pedarla, Aravind; Chittoori, Bhaskar; Ganne, Vijay Krishna; Nazarian, Soheil
For several years reclaimed asphalt pavement (RAP) material has been used as a construction material in hot-mix asphalt (HMA) to reduce material costs and stabilize pavements. Of the 45 million tons of RAP produced every year in the United States, only 33% is being used in HMA. Recent studies have demonstrated that RAP can be used effectively in base layers when it is blended with aggregate base materials and stabilized with cement or fly ash additives. This adoption in the pavement base layer helps maximize the reutilization of RAP material and minimize its disposal in landfills, thereby making it an environmentally friendly practice. However, studies reported so far addressed only the strength and stiffness characteristics of stabilized RAP in base layers in the short term, and not many studies have addressed its long-term behavior. In this study the long-term durability of untreated as well as stabilized specimens was tested by conducting standard durability testing to replicate the moisture fluctuations in the field from seasonal variations. In addition, leachate studies were conducted to examine the effect of rainfall infiltration on the leachability of the cement or fly ash stabilizer from stabilized RAP mixtures. Durability studies revealed a very low volumetric change and good retaining strength at the end of three, seven, and 14 cycles for RAP material from the El Paso, Texas, area, and leachate tests proved that the leaching of cement or fly ash stabilizer from RAP mixes cannot be considered to be a concern for long-term performance. However, approximately 2 years of field infiltration were replicated in the laboratory in this study. Of the several RAP mixtures studied, the mixture composed of 60% RAP and 40% base material with 2% cement was identified as an effective long-term-performing mixture.